ROLE OF TEMOZOLAMIDE IN MACROPROLACTINOMA COMPLICATED BY DOPAMINE AGONIST INTOLERANCE AND REFRACTORY TO SURGERY: A CASE REPORT - Jie, Tan Ying; Ismail, Shartiyah; Merican, Nor Shaffinaz Azmi; Abdullah, Noor Rafhathi Adyani (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Prolactinomas comprise approximately 40% of all pituitary adenomas, the majority of which are treated with dopamine agonists (DAs). Patients who fail conventional treatment may be considered for surgery or radiotherapy. CASE We describe a patient who was treated with temozolamide, an alkylating agent, following multiple DAs intolerances and unsuccessful surgery. A 43-year-old female with secondary amenorrhea, primary infertility and galactorrhea was diagnosed to have macroprolactinoma with a prolactin level of 8143 mIU/L (59-619 mIU/L). Pituitary MRI revealed a parasellar and carvenous sinus soft tissue lesion measuring 1.2 cm (AP) x 1.1 cm (W) x 0.8 cm (CC). Cabergoline was initiated and unfortunately, she developed severe headache and vomiting that necessitated hospitalisation. Similar problems occurred when cabergoline was switched to bromociptine. Due to the side effects, she could not comply with her medications. The prolactin level gradually increased to 11636 mIU/L. Endoscopic transsphenoidal surgery was performed as a salvage treatment. Postoperatively, the prolactin level remained as high as 19722 mIU/L, complicated by secondary hypothyroidism and hypocortisolism. Temozolamide 150 mg/m2 for 5 days every 28 days was initiated with monthly surveillance of parameters. She exhibited good tolerability. Following the 12th cycle of temozolamide, the prolactin was 3956 mIU/L, a rapid 80% reduction from the peak in 1 year. CONCLUSION Temozolamide is an effective alternative in treating prolactinoma after unsuccessful conventional modalities. Future research is needed to establish the role of temozolamide in the treatment algorithm.